PENINGKATAN PRESTASI BELAJAR MATA PELAJARAN IPA POKOK BAHASAN PENCEGAHAN KERUSAKAN LINGKUNGAN DENGAN METODE DISCOVERY LEARNING - Markamah Markamah (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2017)
The aim of the study was to describe the improvement of science learning achievement in the subject of Prevention of Damage to the Environment in the third graders of the state elementary school Plosoboden, Deket Lamongan using the Discovery Learning. This study was designed in a Class Action Research (PTK) within 2 cycles. Each cycle consisted of four stages, namely action planning, action, evaluation, and reflection. The data in this study were collected by observation, documentation, and testing. Student learning outcomes after using Discovery Learning fairly complete. This was evidenced by the significant increase in the average value during the post-test in each cycle, i.e in the first cycle was 70.93, while in the second cycle was 77.81. Thus, the application of methods Discovery Learning can increase learning achievement in material science subjects Environmental Damage Prevention.